(untitled) (Praxis Educativa, 2025)
The National University of Entre Ríos (Argentina) is experiencing institutional reforms, socio-cultural changes, technological innovations and budgetary adjustments. This article explores the perceptions and expectations about the future of higher education of teachers who carry out pedagogical innovation at the university. Based on a qualitative, exploratory and synchronic strategy, semi-structured interviews were conducted with selected teaching teams. As a result, it was found that these teachers emphasized the need to consolidate hybrid or mixed teaching methods, make educational trajectories more flexible and develop practical skills in each subject. However, they also highlighted the importance of face-to-face classes to strengthen technical laboratory skills, the use of specific equipment and to build meaningful learning and socioemotional skills through interaction with others. To this end, they agreed that it is necessary to create conditions for teachers to have more time, dedication and continuous training.